Catalytic Mechanism of Pd Adsorption on S-Terminated GaAs(001)-(2 × 6) Surface - Deng-feng Li; Zhi-cheng Guo; Bo-Lin Li; Ming Luo (Advances in Condensed Matter Physics)
Structural and electronic properties of Pd adsorption on clean and S-terminated GaAs(001)-(2 × 6) surfaces are studied using first-principle simulations. Our calculations show that the Pd atom prefers to occupy the HH3 site. The Pd atom is lower than the S atom with 0.15 Å. The density of states analysis confirms that S–Ga bond plays an important role in Heck reaction. We also find that the Pd catalysis activity for Pd adsorption on clean GaAs(001)-(2 × 6) surface is weak while it is enhanced when the Pd atom is adsorbed on the S-terminated GaAs(001)-(2 × 6) surface, which is in good agreement with the experiments.